Implementation of Sustainable Tourism Policy in Indonesia - Damiasih Damiasih (Journal of Governance, 2023)
Tourism has an important role in the country's economic growth, but its impact on the environment and culture often attracts attention. Therefore, sustainable tourism policies in Indonesia are the focus of the Indonesian government. This research aims to analyze and evaluate the implementation of sustainable tourism policies in Indonesia. This research uses a qualitative approach with descriptive methods. The research results show that the implementation of sustainable tourism policies in Indonesia involves the concept of protecting the environment, improving people's quality of life, and strengthening destination competitiveness. This policy covers waste management, renewable energy, and protection of flora and fauna. Sustainable tourism also contributes to job creation, cultural preservation, and local community participation. Destination competitiveness is enhanced by environmentally friendly infrastructure and the promotion of responsible tourism. The sustainability of natural and cultural heritage is a focus, such as in Komodo and Borobudur National Parks. Partnerships between government, society and the tourism industry are the basis, while technological innovation supports sustainability. Even though there are challenges, joint efforts are expected to be able to overcome obstacles to realizing sustainable tourism in Indonesia.